Menikmati Kopi, Memaknai “Joss” Studi Eksploratif terhadap Pengalaman Wisatawan Domestik didalam Mengonsumsi Kopi Joss - Hartono, Yudo; Wijanarti, Sri Widya (JURNAL MASTER PARIWISATA; Volume 07, Nomor 01, Juli 2020DO - 10.24843/JUMPA.2020.v07.i01.p14, 2020)
This study aims to explore the meaning from the experience of Kopi Joss consumption from domestic tourist’s perspective. Kopi Joss is a name of coffee little shop that called angkringan near Malioboro Street in Yogyakarta. In this study, Holt’s Typology is used to analyze the meaning of the consumption from cultural and social perspective and this research uses qualitative perspective with domain analysis to describe the depth of the data. The result shows Kopi Joss meaning is related to the context where the consumption took place and the result can be used to strengthen the position of Kopi Joss in the future. Keywords:  Kopi Joss, Domain analysis, coffee meaning